Lead, cadmium and arsenic in human milk and their socio-demographic and lifestyle determinants in Lebanon - Elaridi, Jomana (2018)
Introduction Exposure of newborns to toxic metals is of special interest due to their reported contamination in breast milk and potential harm. The aim of this study was to assess the occurrence and factors associated with lead, cadmium and arsenic contamination in breast milk collected from lactating mothers in Lebanon. Methods A total of 74 breast milk samples were collected from primaparas according to guidelines set by the World Health Organization. A survey was administered to determine the demographic and anthropometric characteristics of participating lactating mothers. Dietary habits were assessed using a semi-quantitative food frequency questionnaire. The milk samples were analyzed for the presence of arsenic, cadmium and lead using microwave-assisted digestion and atomic absorption spectrophotometry. Results Arsenic contamination was found in 63.51% of breast milk samples (mean 2.36 ± 1.95 μg/L) whereas cadmium and lead were detected in 40.54% and 67.61% of samples respectively (means 0.87 ± 1.18 μg/L and 18.18 ± 13.31 μg/L). Regression analysis indicated that arsenic contamination was associated with cereal and fish intake (p = 0.013 and p = 0.042 respectively). Residence near cultivation activities (p = 0.008), smoking status before pregnancy (p = 0.046), potato consumption (p = 0.046) and education level (p = 0.041) were associated with lead contamination. Cadmium contamination was significantly associated with random smoke exposure (p = 0.002). Conclusion Our study is the first in Lebanon to report toxic metal contamination in breast milk. Although estimated weekly infant intake of these metals from breast milk was found to be lower than the limit set by international guidelines, our results highlight the need for developing strategies to protect infants from exposure to these hazardous substances.